Low complexity watermarking scheme for scalable video coding - Buhari, A.; Ling, Huo Chong; Baskaran, V.; Wong, K. (2016)
© 2016 IEEE. This paper presents a low complexity human visual system based watermarking algorithm for H.264 spatial scalable coding. The proposed algorithm extracts textural feature from a set of 7 high energy quantized coefficients in 4 × 4 luma INTRA-predicted blocks of all-slices and embeds watermark into the highly textured block which has at least one non-zero coefficient in 6 selected locations. Experiments were conducted by embedding up to 8192 watermark bits into a four-layer spatial scalable coded video. Results suggest that the proposed scheme produces watermarked video with an average visual quality degradation of 0.36 dB at the expense of 2.18% bitrate overhead. In addition, the proposed watermarking scheme achieves the detection rates of 0.96, 0.94 and 0.66 against re-encoding, recompression and Gaussian filtering attacks, respectively.